DIGITAL TAXES AND THE CHALLENGES OF TAX ENFORCEMENT IN INDONESIA’S DIGITAL ECONOMY - Fittry Megasari Sijabat (ADISAM Publisher, 2026)
The development of the digital economy has significantly transformed transaction patterns and business models in Indonesia. These changes present new challenges for the national tax system, particularly regarding the imposition, collection and enforcement of tax laws on digital activities that are cross-border, intangible and highly dynamic. This study aims to analyse the legal framework for digital taxation in Indonesia and to identify the challenges of tax law enforcement in the digital economy era. The method employed is a literature review using a descriptive qualitative approach, involving the examination of various relevant literature, legislation, academic journals, and official sources. The findings indicate that Indonesia has established a legal foundation for digital taxation through various regulations, particularly those relating to the collection of tax on electronic transactions, digital services, and platform-based economic activities. However, its implementation still faces obstacles in the form of difficulties in identifying taxpayers, limited access to data, weak cross-jurisdictional oversight, and the potential for tax avoidance by digital businesses. Therefore, regulatory strengthening, modernisation of tax administration, and international cooperation are required so that digital tax enforcement can be effective, fair, and adaptable to developments in the digital economy.